“Reunian” Perencanaan Hunian Nyaman, Inovasi Pembelajaran melalui Project Based Learning - Anik Rahmawati Wahyuningsih (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Education is a planned effort to create a learning atmosphere that supports the learning process, so that students are motivated to explore their potential actively. During the Covid 19 pandemic, limited time for face-to-face meetings meant that the curriculum achievements were not optimal and subject matter could not be fully conveyed. Some of the material in APLPIB (Software Application and Building Interior Design) subjects can only be conveyed in theory, students do not have time to practice performance. This prompted the author to apply the project-based learning model by implementing good practices REUNIAN, Comfortable Residential Planning: Learning Innovation through Project Based Learning. The purpose of this study was to describe the application of the project-based learning model and the results of its implementation. . The research was conducted at State Vocational School 2 Klaten on DPIB expertise competency (Building Modeling and Information Design), with a qualitative descriptive research method. The application of project-based learning was carried out for 72 class XII DPIB students, who were divided into 15 groups. The results showed that 78.9% of the students looked active and enthusiastic in working on the project given by the teacher. As many as 82.7% of students can show ideas from learning outcomes independently in solving problems in a given project. The results of the project, in the form of 3-dimensional animated pictures of residential houses, are uploaded on social media as a form of appreciation for the students' work.